ChemInform Abstract: Catalytic Hydrogenation of Squalene to Squalane. Issue 50 (16th December 2014) - Ciriminna, Rosaria; Pandarus, Valerica; Beland, Francois; Pagliaro, Mario
Abstract Review: 38 refs.